The Barriers and Facilitators of Different Stakeholders When Deprescribing Benzodiazepine Receptor Agonists in Older Patients—A Systematic Review - Anja Fog Rasmussen; Sarah Sonne Poulsen; Lykke Ida Kaas Oldenburg; Charlotte Vermehren (Metabolites, 2021)
Treatment of older patients with benzodiazepines and Z-drugs (BZRA) is associated with an increased risk of side effects. However, this treatment is still used among these patients. Deprescribing can be a tool to reduce inappropriate medication. This review aims to identify and compare barriers and facilitators of stakeholders involved in BZRA deprescribing in older patients and uncover potential gaps in the research field. The search was conducted in PubMed, EMBASE, PsycINFO, and Cochrane Library. Ten articles based on qualitative data on BZRA deprescribing in older patients (≥65 years) published between 2005–2020 were included. Six articles referred to patients as stakeholders, two referred to physicians, and one to nurses and caregivers, respectively, indicating a need for more studies in the field. More barriers than facilitators were identified. Important findings were the patient willingness to deprescribe BZRA compared to physicians, who did not mention deprescribing to patients due to barriers such as expected patient resistance. Nurses mentioned barriers like lack of knowledge and the feeling that their options were not valued by physicians; education was found to be a shared deprescribing facilitator among the stakeholders. Being aware of deprescribing barriers and facilitators can be helpful in future successful deprescribing interventions.